2022-RA-1187-ESGO Management and outcomes in high risk GTN – a regional cancer center experience. (20th October 2022) - Jain, Neha; Pallavi, VR; Shobha, K; Rajshekhar, K; Vanakudri, Tejas
Abstract : Introduction/Background: GTN is a chemosensitive malignancy with an excellent cure rate. Most women having high risk GTN (HRGTN) are treated with EMACO (etoposide, methotrexate, dactinomycin, cyclophosphamide, and vincristine), however, up to 25% of women with HRGTN have refractory disease & require alternate strategies. Methodology: 74 women with HRGTN treated at our center from 2006 to 2021 were retrospectively analyzed. Patients were initially started on EMACO & those who developed incomplete response or resistance were treated with salvage therapy which included various drug combinations (employing etoposide and platinum agents) and surgery. Results: The mean age of patients was 26.58 ± 6.76 years. Prior pregnancy was molar pregnancy in 33 patients (44.6%), abortion in 32 patients (43.2%), 2 had ectopic pregnancy (2.7%) & 7 had normal delivery (9.45%). Lung metastasis was present in 55 patients (74.32%), 7 had brain metastasis, 4 had vaginal & 3 had liver metastasis. Majority of the patients (66.2%) were in FIGO Stage 3 at the time of diagnosis. All patients received EMACO as the first line chemotherapy, 29 patients (39.2%) developed resistance and received EMA/EP regimen alone in 24 patients and EMA/EP followed by TC in 5 patients. Seventeen patients (23.72%) needed salvage surgery – hysterectomy (12), tumor resection (3) & lung metastatectomy (2) and 7 received brain radiotherapy . Complete response to salvage therapy was seen in 82.5% patients. Majority of patients who received salvage therapy had β-hcg >10 6 mIU/mL (p= 0.023) & had FIGO score ≥12 (0.021). The patients were followed-up till May 2022 – 3 deceased during the course of treatment, 3 patients had recurrence and 7 patients conceived successfully and delivered a live baby. Conclusion: EMACO as first line chemotherapy and platinum/etoposide-based drug regimens along with surgery as salvage therapy in high risk patients were successful in achieving cure in high-risk GTN patients.